Analysis of the current state and prospects for the development of sedatives in the modern Ukrainian pharmaceutical market - S. A. Hladyshevа; Al Nasir Eiad; V. V. Luts; O. P. Hudzenko (Zaporozhye State Medical University, 2021)
Modern research has shown that cognitive impairments are directly related to behavioral disorders and psychopathological syndromes. Nootropic drugs used for pharmacotherapy of cognitive impairments demonstrate low clinical efficiency for the treatment of psychoemotional disorders. In this case, it is advisable to correct such states by prescribing sedatives that have an integrated effect on etiological factors, pathogenetic links and symptomatic manifestations of the disease. The aim of the research was to carry out a comprehensive assortment analysis of sedative drugs within the pharmaceutical market of Ukraine. Materials and methods. Studies were carried out through generally accepted statistical and marketing studies (State Register of Medicines of Ukraine, September, 2020). Our research focused on the information on the structure of the market of sedatives registered in Ukraine. Graphical and logical methods were used in the course of the study. Results. The results of the study have shown that the products manufactured in the Ukrainian pharmaceutical enterprises take 71.50 % of this segment; whereas sedatives produced in Germany - 7.50 %; in Poland - 3.56 %; in Italy, Slovenia, France - 1.50 % for each respectively; in Austria, Malta, Great Britain - 1.02 % for each respectively. The preparations of this group are represented in solid (tablets, coated tablets, capsules, granules, herbs in packs and filter bags) and liquid (tinctures, drops, liquid extracts, elixirs, syrups, oral solutions) dosage forms. Among the studied medicines, solid dosage forms predominate; their share makes 62.7 % of the assortment, and the highest percentage rate is held by tablets (45.5 %). The largest market share of liquid medicinal forms is made by tinctures, in particular 18.9 %. The lowest percentage rates are observed in such medicinal forms as liquid extracts, drops, elixirs, syrups and oral solutions (15.5 % in general). Analysis of the state of the Ukrainian pharmaceutical market of sedatives shows that synthetic drugs account for 24.55 % of the market (tablets - 92.7 %), natural (plant) medicines - 75.45 % (solid dosage forms - 89.6 %). Conclusions. Marketing studies were carried out on the modern market of sedative medicines in Ukraine. It has been established that the quantitative and qualitative diversity of the current assortment is presented by the imported drugs and domestic producers. Analysis of the state of the Ukrainian pharmaceutical market of sedatives was performed. Sedative preparations of natural (plant) origin have been found to be predominant and occupy 2/3 of the total range of sedatives registered in Ukraine as of September, 2020. Synthetic sedative drugs are mainly combined. Monodrugs of plant origin make up the majority of assorted items. Development of drugs aimed at providing complex pharmacotherapeutical correction of cognitive and psychoemotional disorders and based on such peptides as vasopressin, is one of the most significant and relevant problems in modern neurology and is of great scientific and practical value.